신생활운동과 ‘婦女의 신생활’ - 金河林; Kim Harim (중국학보, 2025)
본고는 중국의 1930년대 중반 형성된 여성 담론의 지형과 실천의 의미를 신생활운동의 성격과 이념적 지향에 주목하여 살펴본 연구이다. 이를 통해 ‘신생활운동’과 ‘부녀 문제’의 교차를 사상사의 문맥에서 되묻고 남경국민정부의 여성 주체에 대한 규율 방식을 비판적으로 검토하고자 한다. 이에 첫째, 신생활운동을 계기로 ‘부녀 문제’가 재부상하였음에 주목하여 그것이 가지는 시대적 의미를 살피고, 제도적·인식적 차원에서 여성 관련 의제들이 어떻게 다뤄졌으며 성과와 한계는 무엇이었는지를 젠더화된 국민 형성의 관점에서 접근해 보고자 한다. 둘째, 신생활운동의 담론 지형 속에서 여성국민상이 어떻게 구축되었는지를 다층적으로 검토한다. 중국 여성의 국민적 정체성을 담보할 공통분모로서 ‘가정’이 다시금 주목되게 된 맥락과 이것이 여성과 국가와의 관계 재정립에 어떻게 개입하는지를 살핀다. 또한 신생활운동에서 맥락화된 ‘현모양처’상의 특징을 『婦女新生活月刊』을 중심으로 살펴본다. 이상의 작업을 통해 남경국민정부가 시도한 국민형성 과정에서 여성에 대한 규율의 동력이 여성 담론에 어떤 방식으로 작용하였는지를 비판적으로 검토하고자 한다. 이러한 시도는 신생활운동에 대한 역사적 이해의 지평을 넓히는 것임은 물론, 남경국민정부의 젠더화된 국민 형성의 구체적 양상을 규명하는 데 중요한 밑거름이 될 것이다. This paper examines the discourse on women that emerged during the New Life Movement, focusing on the movement’s ideological orientation and characteristics to explore how the “woman question” was discussed, and to analyze the contours of this discourse and the meanings of its practical application. Through this, the study seeks to reconsider the intersection between the “New Life Movement” and the “woman question” within the context of intellectual history and critically investigate how the Nanjing Nationalist Government sought to regulate female subjectivity. First, it highlights how the “woman question” resurfaced during the New Life Movement and explores its historical significance. It examines how women-related agendas were addressed both institutionally and discursively, assessing their achievements and limitations from the perspective of gendered nation-building. Second, it investigates how the ideal image of the female citizen was constructed within the discursive landscape of the New Life Movement. It analyzes how the “family” was reemphasized as a common denominator that guaranteed Chinese women’s national identity, and how this emphasis mediated a redefinition of the relationship between women and the state. The study also reconstructs the features of the “wise mother, good wife” (賢母良妻) ideal as contextualized in the New Life Movement, with a focus on The Women’s New Life Monthly (婦女新生活月刊). Through this inquiry, the study critically examines how mechanisms of regulation targeting women were mobilized through gendered discourse within the broader process of national formation under the Nanjing Nationalist Government. This attempt not only broadens the historical understanding of the New Life Movement but also offers a critical foundation for revealing the specific modalities of gendered nation-making under the Nanjing regime.